Structural dynamics of innovation networks in German Leading-Edge Clusters - To ¨ pfer, Stefan (Springer Nature, 2020)
We study the effects of a German national cluster policy on the structure of collaboration networks. The empirical analysis is based on original data that was collected in fall 2011 and late summer 2013 with cluster actors (ﬁrms and public research organizations) who received government funding. Our results show that over time the program was effective in initiating new cooperation between cluster actors and in intensifying existing linkages. A substantial share of the newly formed linkages is among actors who did not receive direct funding for a joint R&D project, which indicates a mobilization effect. Furthermore, we observe differential developments regarding clusters’ spatial embeddedness. Some clusters tend to increase their localization, whereas others increase their connectivity to international partners. Changes in centrality are mainly determined by initial positions in the network, but the determinants of these changes differ substantially between clusters.